2016
DOI: 10.1002/ardp.201600008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti‐HIV‐1 Evaluation of Some Novel MC‐1220 Analogs as Non‐Nucleoside Reverse Transcriptase Inhibitors

Abstract: Some novel MC-1220 analogs were synthesized by condensation of 4,6-dichloro-N-methylpyrimidin-2-amine derivatives (1a,b and 15) and/or 4-chloro-6-methoxy-N,N,5-trimethylpyrimidin-2-amine (2a) with the sodium salt of 2,6-difluorophenylacetonitrile followed by treatment with aqueous sodium hydroxide in methanol, alkylation, reduction, halogenation, and/or acidic hydrolysis. All synthesized compounds were evaluated for their activity against HIV-1. The most active compound in this study was compound 7, which show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Nucleoside antiviral medications, commonly used for treating viral diseases like HIV, have been significantly developed, but non-nucleoside analogs have emerged as highly effective antiviral agents. [146] A number of nucleoside and non-nucleoside pyridine analogs 75 a-j (Figure 20) were reported and analyzed by Ibrahim et al based on the facts to test their in vitro antiviral abilities against different DNA-and RNA-virus types. [147] It was shown that the majority of active chemicals are more selective in their inhibition of DNA-virus replication than RNA-virus replication.…”
Section: Antiviral Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleoside antiviral medications, commonly used for treating viral diseases like HIV, have been significantly developed, but non-nucleoside analogs have emerged as highly effective antiviral agents. [146] A number of nucleoside and non-nucleoside pyridine analogs 75 a-j (Figure 20) were reported and analyzed by Ibrahim et al based on the facts to test their in vitro antiviral abilities against different DNA-and RNA-virus types. [147] It was shown that the majority of active chemicals are more selective in their inhibition of DNA-virus replication than RNA-virus replication.…”
Section: Antiviral Agentmentioning
confidence: 99%
“…Nucleoside antiviral medications, commonly used for treating viral diseases like HIV, have been significantly developed, but non‐nucleoside analogs have emerged as highly effective antiviral agents [146] . A number of nucleoside and non‐nucleoside pyridine analogs 75 a – j (Figure 20) were reported and analyzed by Ibrahim et al .…”
Section: Biological Activitymentioning
confidence: 99%
“…Further modificationso ft he lead compound MC-1220 resulted in the identification of 79 and 80 with high potency against the wild-type HIV-1 strain (Figure 38). [50] Good activity profile and high selectivity indices are the essentialf actors for an anti-HIV-1 agent to be used as at opical microbicide. Therefore, to obtain ap otent NNRTI formulated as am icrobicide gel, an ew series of N-DABOs were synthesized.…”
Section: Dihydroalkoxybenzyloxopyrimidine Familymentioning
confidence: 99%
“…Further modifications of the lead compound MC‐1220 resulted in the identification of 79 and 80 with high potency against the wild‐type HIV‐1 strain (Figure ) …”
Section: Modification Of Existing Nnrti Scaffoldsmentioning
confidence: 99%
“…Gene-therapy in recent research was based on DNA and its modification [8][9][10]. The thymidine ring is a DNA building block that interests many researchers to focused their research on the synthesis of new pyrimidine rings as anti-cancer agents such as 5-fluorouracil [1][2][3][4][5][6][7][8][9][10][11][12][13][14], and anti-HIV like AZT, D4T, Nikavir [15][16][17][18][19][20][21], Lamivudina [22] and Emtricitabina [16,[23][24]. The Nitrogen containing heterocycles like pyrimidines and their derivatives have received great attention for their considerable exciting biological activities [25][26][27][28].…”
Section: ■ Introductionmentioning
confidence: 99%